Isolation of bacteriophages infecting Xanthomonas oryzae pv. oryzae and genomic characterization of novel phage vB_XooS_NR08 for biocontrol of bacterial leaf blight of rice - Jain, Lata; Kumar, Vinay; Jain, Sanjay Kumar; Kaushal, Pankaj; Ghosh, Probir Kumar (Frontiers in Microbiology, 2023)
Bacterial leaf blight (BLB) disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most destructive diseases worldwide in rice-growing regions. Ineffectiveness of chemicals in disease management has increased the interest in phage therapy. In this study, we isolated 19 bacteriophages, infecting Xoo, from rice field which belonged to phage family Siphoviridae, Myoviridae and Podoviridae on basis of electron microscopy. Among 19 phages, Phage vB_XooS_NR08 a member of Siphoviridae family expressed antibacterial activity towards all Xoo strains tested and did not lyse X. campestris and other unrelated bacterial host. Phage NR08 showed more than 80% viability at temperature range 4-40 °C, pH range 5-9 and direct exposure to sunlight for 2 h whereas UV light and chemical agents were highly detrimental. In one step growth curve, NR08 have 40 min latent period followed by 30 min burst period with burst size 250 particle/bacterium. The genome of NR08 is double-stranded DNA, linear having size 98812 bp with G+C content 52.9%. Annotation of the WGS indicated that NR08 encodes 142 putative open reading frames (ORFs) including one ORF for tRNA namely trna1-GlnTTG. Comparative genome analysis of NR08 showed that it shares maximum similarity with Pseudomonas phage PaMx42 (40 % query coverage, 95.39 % identity, acc. length 43225) and Xanthomonas phage Samson (40 % query coverage, 96.68 % identity, acc. Length 43314). The average alignment percentage of NR08 with other Xoophages was only 0.32 to 1.25 since the genome of NR08 (98.8 kb) is almost double of the most of the previously reported Xoophages (43-47 kb) thus indicates NR08 as novel Xoophage. In in vitro bacterial challenge assay, NR08 showed bacteriostasis up to 24 h and 99.95% reduction in bacterial growth in 48 h. In rice pot efficacy trials, single dose treatment using neat NR08 showed significant reduction in disease up to 90.23% and 79.27% on 7 dpi and 21 dpi, respectively. However, treatment using 2% skim milk supplemented phage preparation was significantly less effective as compared to the neat phage preparation. This study characterized a novel Xoophage having potential as bio-control agent in mitigation of BLB in rice.